IMPACT OF THE ORIGINATING MARTENSITIC PHASE ON THE CHARACTER OF MARTENSITIC PHASE TRANSFORMATION - Svetec, Milan (Anali PAZU, 2023)
In the article, we discuss the influence of the locally perturbed order parameter in austenitic-martensitic phase transformation on the character of the phase transformation. We choose Landau type mean field approximation which covers the most important features of the proposed theoretical description.